Grain size modification in the magnetocaloric and non-magnetocaloric transitions in La0.5Ca0.5MnO3 probed by direct and indirect methods - Quintero, Mariano Horacio; Passanante, Sebastian Eduardo; Irurzun, Ignacio José; Goijman, Dafne Yael (American Institute of Physics, 2014)
Fil: Quintero, Mariano Horacio. Comisión Nacional de Energía Atómica. Gerencia del Área de Investigaciones y Aplicaciones no Nucleares. Gerencia de Física (Centro Atómico Constituyentes); Argentina. Universidad Nacional de San Martín. Escuela de Ciencia y Tecnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina